2022
DOI: 10.1209/0295-5075/ac8c69
|View full text |Cite
|
Sign up to set email alerts
|

Probing the response of metals to low-frequency s-polarized evanescent fields

Abstract: Experimental test for the response function of metals to the low-frequency s-polarized evanescent waves is proposed by measuring the lateral component of magnetic field of an oscillating magnetic dipole spaced above a thick metallic plate. This suggestion is motivated by the fact that the Lifshitz theory using the Drude response function is in contradiction with high-precision measurements of the Casimir force performed at separations exceeding 150 nm. Analytic expressions for the lateral components of the magn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…Despite the fact that there are many experiments mentioned above, which demonstrate the failure of the Drude model resulting from the region of transverse electric evanescent waves, it would be highly desirable to perform one more independent test disconnected with the Casimir effect. Recently such an alternative test in the field of classical electrodynamics was proposed in [59,71]. It was shown that the lateral components of magnetic field of an oscillating magnetic dipole spaced in the proximity of metallic plate are determined by solely the transverse electric evanescent waves.…”
Section: Discussion: Failure Of the Drude Model For Transverse Electr...mentioning
confidence: 99%
“…Despite the fact that there are many experiments mentioned above, which demonstrate the failure of the Drude model resulting from the region of transverse electric evanescent waves, it would be highly desirable to perform one more independent test disconnected with the Casimir effect. Recently such an alternative test in the field of classical electrodynamics was proposed in [59,71]. It was shown that the lateral components of magnetic field of an oscillating magnetic dipole spaced in the proximity of metallic plate are determined by solely the transverse electric evanescent waves.…”
Section: Discussion: Failure Of the Drude Model For Transverse Electr...mentioning
confidence: 99%
“…The brief presentation of the part of obtained results related to the lateral component of the field of magnetic dipole is published in the form of a letter in [73].…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesized that the above problems derive from the fact that the Drude model is not applicable in the area of the low-frequency s-polarized evanescent waves, where it has no sufficient experimental confirmation [69,70]. An experiment was proposed allowing one to check this hypothesis [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that the above problems derive from the fact that the Drude model is not applicable in the area of the low-frequency s-polarized evanescent waves, where it has no sufficient experimental confirmation [69,70]. An experiment was proposed allowing one to check this hypothesis [69,70]. The possible resolution of the problem might be found in the search for spatially nonlocal generalizations of the Drude model at low frequencies [71,72].…”
Section: Discussionmentioning
confidence: 99%